2007
DOI: 10.1097/dad.0b013e318156e0a7
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of the Epidermis: A Criterion in the Differential Diagnosis of Melanoma and Dysplastic Nevi That is Associated With Increasing Breslow Depth and Ulceration

Abstract: Consumption of the epidermis (COE), defined as thinning of the epidermis with attenuation of basal and suprabasal layers and loss of rete ridges adjacent to collections of melanocytes, is a recently coined term encompassing changes of the epidermal architecture associated with melanoma. To evaluate this feature as an additional diagnostic criterion for melanoma, we examined COE in 453 melanocytic lesions, including 213 invasive melanomas from a population-based series and 240 suspicious pigmented lesions from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
4
13
2
2
Order By: Relevance
“…a controversial issue regarding prognosis is whether brisk lymphocytic infiltration which tends to limit the increase in primary melanoma thickness has prognostic significance as generally accepted (7 (4). We found a correlation between the presence of CoE and lymphocytic infiltration density in this study but it was not statistically significant .…”
Section: Discussioncontrasting
confidence: 51%
“…a controversial issue regarding prognosis is whether brisk lymphocytic infiltration which tends to limit the increase in primary melanoma thickness has prognostic significance as generally accepted (7 (4). We found a correlation between the presence of CoE and lymphocytic infiltration density in this study but it was not statistically significant .…”
Section: Discussioncontrasting
confidence: 51%
“…These figures are in line with those reported in other studies (11,13). Consumption was first defined and introduced as an important factor for differentiating melanomas from Spitz nevi (10), whereas Walters et al showed a correlation between COE and ulceration (11). In this latter study, COE was frequently found at the edges of ulcerated areas and it was thought of as an early step in the progression toward ulceration (8).…”
Section: Consumption Of the Epidermis:a Possible Precursor Of Ulceratsupporting
confidence: 81%
“…These figures are in line with those reported in other studies (11,13). Consumption was first defined and introduced as an important factor for differentiating melanomas from Spitz nevi (10), whereas Walters et al showed a correlation between COE and ulceration (11).…”
Section: Consumption Of the Epidermis:a Possible Precursor Of Ulceratsupporting
confidence: 80%
See 1 more Smart Citation
“…Their data suggested that consumption is a useful criterion for the diagnosis of melanocytic neoplasms. Subsequently, Walters et al carried out a population‐based study in which consumption was identified in 92/213 (43%) invasive melanomas and became progressively more frequent with increasing Breslow depth (p < 0.0001) and Clark level (p = 0.0002) 6 . These results were interesting, but this series included only two cases of acral lentiginous melanoma (ALM), which is the most common type of melanoma in Japan 7 .…”
mentioning
confidence: 97%